HydroTi: An Irrigation System for Urban Green Areas using IoT - Carrillo-Pasiche, Piero (2022)
Irrigation systems and their performance to efficiently accomplish their function have gained notoriety in recent years. Therefore, those systems are not capable of approaching many factors as water-saving and irrigation automation. Here we present a new irrigation system based on the IoT, analyzing the most important factors that involve an efficient irrigation process taking into consideration water usage and saving this resource. Thus, we developed a prototype using Arduino Uno which is connected to sensors that can lead a web application named HydroTi to determine when to irrigate and how much water to use. This function was enabled by Adafruit IO, a web service useful for IoT projects. To validate the effectiveness of this solution, we compared different irrigation types to determine that the automatic irrigation mode of HydroTi is better w.r.t. water consumption in Metropolitan Lima, Peru urban areas.